AYURVEDIC HEALTH TOURISM MARKETING: AN IN-DEPTH STUDY OF AYURVEDIC HEALTH TOURISM CENTERS IN KERALA - V A, Arunkumar; Rose, G. Jerin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ayurveda is one of the eminent ancient systems of medication that has endured and flourished for centuries to date. It has given a well-deserved boost due to a significant change in the approach of individuals towards supporting the use of natural drugs. Kerala is the heavenly kingdom of Ayurveda as it is sacred, has perfect weather, and has plenty of natural herbs. The study covers the perception of the management of Ayurvedic health tourism centers towards the marketing environment. Besides, the study focuses on customer satisfaction, the factors influencing customer satisfaction, and the factors that motivate tourists to select Ayurvedic health tourism from Kerala. Thus, the study concentrates on two aspects: Ayurvedic health tourism centers and foreign and domestic tourist patients.